AN ANALYSIS ON THE FACTORS WHICH INFLUENCE FINANCIAL STATEMENT QUALITY OF SKPD (REGIONAL WORK UNIT) AT THE BINJAI MUNICIPAL ADMINISTRATION WITH ORGANIZATIONAL COMMITMENT AS MODERATING VARIABLE - Devi, Prima Citra (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of this study was to analyze the influence of the competence of financial management officer, regulation, the role of internal audit, and the utilization of information technology with organizational commitment as moderating variable on the quality of financial statement of Binjai Government. The study used causal research method. The population was 99 people from 33 SKPDs (Regional Work Unit) that consisted of Head SKPD as the official budget users, PPK-SKPD (Financial Management Official of SKPD), and treasurers of Binjai Government, and all of them were used as the samples (census sampling). Primary data were gathered by using questionnaires. Hypothesis was tested by using multiple regression analysis and residual test with an SPSS software program. The result of the study showed that the competence of financial management officer, regulation, and the utilization of information technology had significant influence on the quality of financial statement simultaneously. Partially, the competence of financial management officer, regulation, and the utilization of information technology had significant influence on the quality of financial statement while the role of internal audit had no significant influence on the quality of financial statement. Organizational commitment as moderating variable could moderate the correlation of the competence of financial management officer, regulation, the role of internal audit, and the utilization of information technology with the quality of financial statement of Binjai Government.